Testing Antibacterial Activity of Daun Kentut (Paederia foetida L.) Leaf Extract against Escherichia coli in Vitro - Savitri, Lisa; Tiyas, Eka Wahyuning; Krissanjaya, Rochmad (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Escherichia coli is a pathogenic bacterium that causes infectious diseases in the digestive tract and can produce Lipopolysaccharide (LPS), including lipid A. Exposure to endotoxins in lipid A, can cause systemic effects, such as sepsis, which can lead to clinical manifestations and even death. Daun Kentut (Paederia foetida L.) is one of the herbal plants containing bioactive compounds that can inhibit the growth of E. coli bacteria. The aim of this research is to determine the effective concentration of daun kentut leaf extract to inhibit E. coli growth. This study is an experimental research using maceration extraction method and antibacterial disc diffusion method with 3 repetitions at concentrations of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%, negative control (aquadest), and positive control (ciprofloxacin) conducted from March to April 2023 in the Microbiology Laboratory of Kadiri University. The observation results of inhibition zones in each treatment varied. The presence of these inhibition zones is due to the presence of secondary metabolite compounds in daun kentut leaf extract that have antibacterial activity, such as inhibiting protein synthesis mechanisms, causing damage to cell wall permeability, and ultimately leading to bacterial cell lysis and death. The statistical analysis using the One Way Anova test with a P-value of 0.05 shows that each variable has significant differences and effects. Thus, it can be concluded that the effective extract variation is the 100% concentration because, in this study, the 100% concentration has an inhibition zone of 26.72 mm and is classified as very strong in inhibiting E. coli bacteria.